Kualitas Nata de Apple dengan Perbedaan Varietas Apel (Malus sylvestris Mill) dan Macam Gula Berdasarkan Tebal, Berat dan Kadar Serat - Fitriyah, Rofiqoh Lailatul; Hastuti, Utami Sri; Witjoro, Agung (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2019)
Apple has the most fruit productio at Batu City. There are two apple varieties; Manalagi cherry and Anna, but some apple varieties have low quality (grade D). The reason is because of low price and the consumers is not interesting to buy, so grade D apple decreased. An alternative to apply the grade D apple is by using for nata production with addition three sugar sort, that is cane sugar, palm sugar and siwalan sugar as a food diversification. This study aims to (1) examine the effect of varieties of apples on the quality of nata based on the weight, thickness and fiber content, (2) to examine the effect of three kinds of sugar on the quality of nata based on the weight, thickness and fiber content , (3) to analyze the difference effect of apples varieties and sugars sort that produce the highest quality nata. The results showed that (1) the apples varieties has significant effect on the nata quality based on the nata fiber content, but there is no significant effect of apples varieties on the nata quality based on the thickness and weight of nata. varieties Manalagi cherry variety produces the best nata quality based on the fiber content, (2) The sugar sorts significantly affect to the nata quality based on thickness, weight and nata fiber content. The use of palm sugar produces the best nata quality based on the thickness, weight and fiber content, (3) The interaction of apple varieties and sugars sorts significantly affect to the nata quality based on the thickness, weight and nata fiber content. Manalagi cherry variety with the addition of palm sugar gives the best nata quality based on the thickness, weight and fiber content